Percutaneous ablation techniques for renal cell carcinoma: current status and future trends. (1st October 2019) - Filippiadis, D.; Mauri, G.; Marra, P.; Charalampopoulos, G.; Gennaro, N.; De Cobelli, F.
Abstract: Percutaneous ablation is an increasingly applied technique for the treatment of localized renal tumors, especially for elderly or co-morbid patients, where co-morbidities increase the risk of traditional nephrectomy. Ablative techniques are technically suited for the treatment of tumors generally not exceeding 4 cm, which has been set as general consensus cutoff and is described as the upper threshold of T1a kidney tumors. This threshold cutoff is being challenged, but with still limited evidence. Percutaneous ablation techniques for the treatment of renal cell carcinoma (RCC) include radiofrequency ablation, cryoablation, laser or microwave ablation; the main advantage of all these techniques over surgery is less invasiveness, lower complication rates and better patient tolerability. Currently, international guidelines recommend percutaneous ablation either as intervention for frail patients or as a first line tool, provided that the tumor can be radically ablated. The purpose of this article is to describe the basic concepts of percutaneous ablation in the treatment of RCC. Controversies concerning techniques and products and the need for patient-centered tailored approaches during selection among the different techniques available will be discussed.